Macroeconomic determinants of economic growth in Indochina countries : a panel analysis - Voon, Jan Na (University Malaysia Sarawak, UNIMAS., 2011)
This study examines the main macroeconomic determinants of economics growth in Indochina courtries, namely Cambodia, Laos, Myanmar, Thailand and Vietnam over the period of 1980 to 2009 where the sample period is dictated by data availability. Various econometics methodologies like Levin, Lin and Chu (LLU), Im, Pesaran and Shin (IPS) and Fisher-type (Fisher-ADF and Fisher-PP) panel unit root tests, Pedroni's cointegration test and Hausman test are conducted in this study.